2018
DOI: 10.1111/1440-1681.13000
|View full text |Cite
|
Sign up to set email alerts
|

Increases in placental nitric oxide, but not nitric oxide‐mediated relaxation, underlie the improvement in placental efficiency and antihypertensive effects of hydrogen sulphide donor in hypertensive pregnancy

Abstract: Dysregulation of hydrogen sulphide (H S) producing enzymes has been related to hypertensive pregnancy, and H S donor, sodium hydrosulphide (NaHS) exerts antihypertensive effects, modulates angiogenic factors production and acts as an antioxidant. Moreover, reduction in nitric oxide (NO) bioavailability is related to hypertensive pregnancy and H S may interact with NO, modulating its production. We aimed to investigate the NaHS effects in hypertension-in-pregnancy and also in feto-placental parameters. Female W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…In line with previous findings, foeto‐placental growth restriction with concomitant elevations in systolic blood pressure, in plasma sFlt‐1/PlGF ratio and in oxidative stress was observed here (HTN‐Preg group). Also, we found impaired endothelium‐mediated vasodilation in response to acetylcholine and hyper‐reactivity in the contractile response to phenylephrine in thoracic aorta rings of the HTN‐Preg group, as previously reported . In addition, although KCl‐induced contraction responses suggest that vascular calcium influx through voltage‐gated calcium channels could not be behind hyper‐reactive response to phenylephrine observed in the HTN‐Preg group, it is possible that phenylephrine had further activated calcium influx through receptor and store‐operated calcium channels, and thus, a greater calcium influx could have occurred in HTN‐Preg rats.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In line with previous findings, foeto‐placental growth restriction with concomitant elevations in systolic blood pressure, in plasma sFlt‐1/PlGF ratio and in oxidative stress was observed here (HTN‐Preg group). Also, we found impaired endothelium‐mediated vasodilation in response to acetylcholine and hyper‐reactivity in the contractile response to phenylephrine in thoracic aorta rings of the HTN‐Preg group, as previously reported . In addition, although KCl‐induced contraction responses suggest that vascular calcium influx through voltage‐gated calcium channels could not be behind hyper‐reactive response to phenylephrine observed in the HTN‐Preg group, it is possible that phenylephrine had further activated calcium influx through receptor and store‐operated calcium channels, and thus, a greater calcium influx could have occurred in HTN‐Preg rats.…”
Section: Discussionsupporting
confidence: 82%
“…Briefly, conscious rats were first acclimated in a quiet room, conditioned and restrained in a warm‐box (Insight, Ribeirao Preto, Sao Paulo, Brazil, catalogue #EFF‐307) at 40°C for 5‐10 min. Systolic blood pressure was determined as the average of the cuff inflation–deflation (3‐6 cycles) by a trained operator . Measurements on gestational days 14, 16 and 19 were performed 3 hr before drug or saline administrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we previously showed that L-NAME-induced hypertension in late pregnant rats triggered the increases in MMP-2 and -9 activities in placenta and MMP-2 in uterus and these changes were associated with angiogenic imbalance which was featured by increase in soluble fms-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PLGF) [77]. Moreover, we also observed in another previous investigation that increases in placental NO levels underlie the improvement in placental efficiency in late hypertensive pregnant rats [86].…”
Section: Discussionmentioning
confidence: 70%
“…Several lines of evidence indicate that H 2 S has a role in the regulation of vascular tone. H 2 S induced vascular relaxation in aorta [ [78] , [79] , [80] ], gastric artery [ 81 ], mesenteric artery [ 5 , 82 ], and internal mammary artery [ 83 ]. Accumulative evidence indicate that H 2 S is an EDHF [ 5 , [17] , [18] , [19] , [20] , 82 , [84] , [85] , [86] ].…”
Section: H 2 S Is An Endothelium-derived Hyperpolamentioning
confidence: 99%